2009
DOI: 10.1111/j.1540-8159.2009.02477.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Acute Ventricular Volume Changes by Intracardiac Impedance in a Chronic Heart Failure Animal Model

Abstract: The strong correlation with SV allows the application of intracardiac impedance measurements for an implant-based continuous monitoring of cardiac function. Impedance may also be used for hemodynamic optimization of cardiac resynchronization therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Stahl et al 17 showed a strong correlation between intracardiac impedance parameters and stroke volume in a porcine model. Panescu et al 18 examined multiple impedance vectors derived from implanted biventricular implantable cardioverter-defibrillator devices in a canine/ovine model of heart failure, and demonstrated good correlation between cardiogenic impedance and progression of heart failure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Stahl et al 17 showed a strong correlation between intracardiac impedance parameters and stroke volume in a porcine model. Panescu et al 18 examined multiple impedance vectors derived from implanted biventricular implantable cardioverter-defibrillator devices in a canine/ovine model of heart failure, and demonstrated good correlation between cardiogenic impedance and progression of heart failure.…”
Section: Discussionmentioning
confidence: 97%
“…Cardiogenic impedance reflects the volumetric fluctuations within the heart during the cardiac cycle and has been used to monitor cardiac contraction in an animal model. 17 This method therefore has the potential to be used for device optimization and may be performed using the device alone, without other specific equipment. Furthermore, as the impedance data are acquired from leads positioned within and on the surface of the heart, this technique should be more specific than the use of trans-thoracic impedance.…”
Section: Introductionmentioning
confidence: 99%
“…20 A positive correlation between LV impedance fluctuation and stroke volume and a negative correlation between diastolic impedance and pressure have been reported in animal experiments using LV electrodes placed on the epicardial surface, outside the cardiac veins. 2123 In other studies, quadripolar systems involving transvenous LV leads have been applied for impedance recording between RV and LV. 24,25 In these cases, however, it is impossible to tell if the transventricular impedance signal reflects the activity of the LV, RV, or both.…”
Section: Discussionmentioning
confidence: 99%
“…In other animal models, intracardiac impedance measured between the LV and RV leads in a CRT platform has also been closely correlated with end-diastolic volume, end-diastolic pressure, 37 stroke volume, and LV dP/dt max . 38 Furthermore, in patients undergoing CRT device implantation, intracardiac impedance (LV-RV) is more closely correlated with echocardiographic changes in LV volume than intrathoracic impedance (RV-can). 39 These findings suggest that changes in LV volume and pressure conditions may produce a more profound change in impedance along the LV-RV vector, encompassing only cardiac tissue, as opposed to the RV-can vector, which encompasses a larger area of noncardiac tissue and may be less sensitive to minute changes in LV loading conditions.…”
Section: Merchant Et Al Implantable Sensors For Heart Failurementioning
confidence: 99%